High-quality synthesized face sketch using generative reference prior - Mahfoud, Sami; Bengherabi, Messaoud; Daamouche, Abdelhamid; Boutellaa, Elhocine; Hadid, Abdenour (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Face sketch synthesis (FSS) is considered an image-to-image translation problem, where a face sketch is generated from an input face photo. FSS plays a vital role in video/image surveillance-based law enforcement. In this paper, motivated by the recent success of generative adversarial networks (GAN), we consider conditional GAN (cGAN) to approach the problem of face sketch synthesis. However, despite the powerful cGAN model ability to generate fine textures, low-quality inputs characterized by the facial sketches drawn by artists cannot offer realistic and faithful details and have unknown degradation due to the drawing process, while high-quality references are inaccessible or even nonexistent. In this context, we propose an approach based on generative reference prior (GRP) to improve the synthesized face sketch perception. Our proposed model, which we call cGAN-GRP, leverages diverse and rich priors encapsulated in a pre-trained face GAN for generating highquality facial sketch synthesis. Extensive experiments on publicly available face databases using facial sketch recognition rate and image quality assessment metrics as criteria demonstrate the effectiveness of our proposed model compared to several state-of-the-art methods.